(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
Lotus root-like fibers and hollow structure fibers have been extensively studied in many different fields due to a large specific surface area and high porosity. However, most of the prepared materials have only one lotus root-like or hollow structure. Here, in this paper, the coaxial electrospinning poly(lactic acid) (PLA) nanofibers had hollow and lotus root-like structures. The porosity of the cross section was quantitatively analysed by MATLAB, and the oil sorption experiment was also carried out. In the hollow structure, when the flow rate ratio of the core/shell solution was 1:2 or 1:4, the pore porosity was about 41%, larger than 34.88% (1:3), while the pore porosity at 19-22 kV was stable at about 41% ± 2%. On the contrary, the lower the porosity, the better the spinning state and the higher the hollow ratio. In the lotus root-like fibers, the porosity values were about 23% ± 2% under different spinning conditions, which means that the lotus root-like porosity was not significantly affected by the flow rate ratio of core/shell solution and voltage. Meanwhile, the absorption capacity of the lotus root-like fibers to diesel oil is more than 1.5 times that of hollow fibers.